2022
DOI: 10.1039/d1ra08935h
|View full text |Cite
|
Sign up to set email alerts
|

On crystallization of water confined in liposomes and cryoprotective action of DMSO

Abstract: Ice-free phase formed by DMSO acting as a protective layer of lipid membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Given the broadening of the endothermic peak and the changes in T m and Δ H fus as shown in Figure d, e, we speculate that the unfrozen water content of the OE 2 imC 3 C solution is higher than that of the two CPA solutions. The fraction of unfrozen water ( U ) in each solution was determined using the following equation U = 1 normalΔ H exp normalΔ H 0 Here, Δ H exp represents the experimentally determined enthalpic change during ice melting, normalized to the weight of water in the solution.…”
Section: Resultsmentioning
confidence: 99%
“…Given the broadening of the endothermic peak and the changes in T m and Δ H fus as shown in Figure d, e, we speculate that the unfrozen water content of the OE 2 imC 3 C solution is higher than that of the two CPA solutions. The fraction of unfrozen water ( U ) in each solution was determined using the following equation U = 1 normalΔ H exp normalΔ H 0 Here, Δ H exp represents the experimentally determined enthalpic change during ice melting, normalized to the weight of water in the solution.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, notwithstanding Me 2 SO can contribute to the amorphous phase formation, DSC and, especially, TMA, Me 2 SO alone cannot inhibit the process. The amorphous phase formation is generally considered a good prognostic factor for promoting cell survi val [35]. However, the work has shown that not all polymers were equally effective in terms of cell recovery after cryopreservation.…”
Section: Resultsmentioning
confidence: 99%
“…Similar depressions of nucleation and melting temperature were reported in some works for water-Me 2 SO systems. 37 The effect of 10% FBS or 100 mg/mL of poly-mers alone (without Me 2 SO) on the melting temperature of Ham's F12 was undetectable by cryomicroscopy itself (Table 3).…”
Section: Ta B L Ementioning
confidence: 97%